Acute Effects of Different Inter-Repetition Rest Intervals During 'Composite' Training on Fast Stretch-Shortening Cycle and Neuromuscular Performance in Hurling Players: A Pilot Study - Luke Atkins; Rodrigo Ramirez-Campillo; Jeremy Moody; Colin Coyle; Paul Byrne (International Universities Strength and Conditioning Association, 2024)
One study to date has compared inter-repetition rest intervals when employing 'composite' training. Thus, the purpose of this study was to compare the acute effects of 2-, 3- and 4-mins 'composite' training inter-repetition rest intervals on fast stretch shortening cycle (SSC) and neuromuscular performance. A randomized crossover research design was employed. Drop jump (DJ), 20m sprint (with 5 and 10m splits), countermovement jump (CMJ) and isometric mid-thigh pull (IMTP) tests were performed pre-session, post-session, and 7 days post-session to observe if supercompensation occurred. A 2-min rest interval showed enhancements in fast SSC DJ performance where supercompensation may have occurred in height, velocity, force and power (Cohen's d = 0.22-0.55). A 3-minute rest interval elicited responses in 5 and 20m sprint performance (Cohen's d = -0.29 to -0.30) and isometric RFD (Cohen's d = 0.35-0.60) 7 days post-session. CMJ measures (Cohen's d = 0.22-0.76) appeared to have experienced supercompensation when employing a 4-minute rest period. Significant (p < 0.05) decreases in performance pre- to post-session were found for certain sprint, CMJ and IMTP variables. The 'composite' training inter-repetition rest interval used, appears dependent on the primary goal of a training cycle. However, a 3-min rest interval may be used if there are multiple goals of a training cycle due to enhancements in sprint performance, isometric RFD and CMJ height. 'Composite' training is a time-efficient method of enhancing jump, sprint, and maximal strength, which is suitable for practitioners working in sports such as hurling where time is limited.